PENYULUHAN CARA MENCUCI TANGAN DENGAN BENAR PADA ANAK TK SEBAGAI UPAYA MENINGKATKAN PERILAKU HIDUP BERSIH DAN SEHAT - Putri Renata Salsabella; Suprihartini, Cucuk; Palupi, Mirthasari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
In P2MD activities, it created a program to strengthen tourism potential, education, and diversify honey as Coduzinc "Zinc Honey Cookies" in Kampung Madu, Bringin Village, Badas District. Activities in this program are in the form of strengthening the potential of educational tourism by making tourism education in which there will be various educations such as education on making Coduzinc "Zinc Honey Cookies", education on how to grow rice, education on how to raise bees to produce honey and there is also health counseling about washing hands properly. From observations at the opening of coduzinc educational tours, there were still some children who washed their hands in an inappropriate way. Therefore, from these problems, health counseling was carried out about washing hands properly to improve children's knowledge and skills about washing hands